Failure rate of the pulmonary embolism rule-out criteria rule for adults 35 years or younger: Findings from the RIETE Registry - Jossein T; Mazzolai L; Lorenzo Hernández A; Zdraveska, Marija; Rivas Guerrero A; López Ruiz A; Di Micco P; Monreal M; Hugli O (Wiley (United States), 2025)
Background The use of a computed tomography pulmonary angiogram to diagnose pulmonary embolism (PE) has increased, leading not only to higher PE diagnoses but also to overdiagnosis and unnecessary radiation exposure, even in young patients despite a lower PE incidence. The aim of this study was to assess the failure rate of the pulmonary embolism rule-out criteria 35 (PERC-35) rule developed to reduce unnecessary testing in individuals aged ≤35 years among patients included in the Registro Informatizado de la Enfermedad TromboEmbolica Venosa (RIETE) Registry. Methods This retrospective cohort study used data from the RIETE Registry, an ongoing, international prospective registry of patients with objectively confirmed venous thromboembolism. The primary outcome was the missed PE rate using PERC-35 criteria. Secondary outcomes included the comparison of demographic and clinical characteristics, PE localization, treatment strategies, and outcomes between PERC-negative (PERC-35N) versus PERC-positive (PERC-35P) patients. Results Of 58,918 adult patients with acute PE, the PERC-35 rule demonstrated a low missed PE rate of 0.35% (n = 204), with an upper 95% confidence interval [CI] of 0.40%. The missed rate was 7.0% (95% CI 6.0%–7.9%) in the 18- to 35-year subgroup. Compared to PERC-35P patients, PERC-35N patients were younger (mean age 28.4 years), with a lower body mass index, and included a higher proportion of pregnant/postpartum women. PERC-35N patients had a significantly lower rate of chronic diseases and presented less frequently with dyspnea or syncope but more often with chest pain. They showed lower rates of positive D-dimer and troponin levels. PERC-35N patients experienced fewer major bleeding episodes, similar recurrence rates of PE/deep vein thrombosis, and no deaths during anticoagulation. Conclusions The PERC-35 rule demonstrated a low failure rate to exclude PE in patients aged 18–35 years and could reduce imaging and radiation exposure in young patients with a low PE pretest probability if confirmed prospectively.
Keywords: diagnostic algorithm; PERC; pretest probability; pulmonary embolism; pulmonary embolism rule-out criteria rule; RIETE